Answers

The Brainliest Answer!
2014-07-24T15:54:26+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Using cosine rule in a triangle ABC and triangle ABD  (D = mid point of BC, E = mid point of AC, and F = mid point of AB)
cos B = (AB² + BC² - AC² ) / 2 AB * AC
cos B = (AB² + BD² - AD² ) / 2 AB *  AD
   equating both sides, replace BD = BC/2  we get
   2 AB² + 2 AC² = 4 AD² + BC²            write now AD =  GA + GD  = (3/2) GA
                         = 4 (9/4 GA² ) + BC² = 9 GA²+ BC²
  similarly  2 AB² + 2 BC²  =9 GB2  + AC2
           2 BC² + 2 AC² = 9 GC2 + AB2
Add the three equations
   you get answer
 
1 5 1